A multicenter phase 4 geriatric assessment directed trial to evaluate gemcitabine +/− nab-paclitaxel in elderly pancreatic cancer patients (GrantPax) - Betge, Johannes; Chi-Kern, Jing; Schulte, Nadine; Belle, Sebastian; Gutting, Tobias; Burgermeister, Elke; Jesenofsky, Ralf; Ebert, Matthias; Härtel, Nicolai (BMC cancer, 2018)
In the group of elderly patients (≥70 years) with metastatic pancreatic ductal adenocarcinoma (mPDAC), it is not known who benefits from intensive 1st line nab-paclitaxel/gemcitabine (nab-p/gem) combination chemotherapy or who would rather suffer from increased toxicity. We aim to determine whether treatment individualization by comprehensive geriatric assessments (CGAs) improves functional outcome of the patients.